Analysis of the Cutting Parameters in Front Milling for Medium Density Fiberboard - Deus, Priscila R.; Alves, Manoel C. S. [UNESP]; Vieira, Fabio H. A.; Bilesky, Luciano R. (North Carolina State Univ Dept Wood & Paper Sci, 2018)
Medium density fiberboard (MDF) is an industrial product manufactured from lignocellulosic fibers. It has homogeneity, dimensional stability, and mechanical strength compared with solid wood. Milling is a machining method widely used in the furniture industry; despite the relevance of the subject, there are few works dealing with the specific MDF milling process using computerized numerical control (CNC) machines. This study evaluated MDF milling in CNC machining centers by analyzing roughness. The MDF panels were front direction with the machined cut depth of 3 mm with six replicates, four cutting speeds of 804 m/min, 603 m/min, 402 m/min, and 201 m/min, and one forward speed of 4 m/min. The parameter of roughness average (R-a) was analyzed. The results showed that the surface roughness showed lower values for the cutting speeds of 603 m/min and 804 m/min, and cutting depths of 3 mm exhibited satisfactory results for the front surface. In conclusion, the parameters studied here significantly influence the finish, resulting in uneven surfaces that can reduce the quality of products.
Keywords: Panels; Roughness; Finishing wood; Wood